Silicon Supplementation Modulates Physiochemical Characteristics to Balance and Ameliorate Salinity Stress in Mung Bean - Al Murad, Musa; Muneer, Sowbiya (Frontiers in Plant Science, 2022)
Mung bean is a low-cost high-protein legume that is sensitive to salinity. Salt stress has been demonstrated to be mitigated by silicon (Si). In legumes, the potential for silicon (Si)-mediated abiotic stress reduction has mainly been ignored. Moreover, there is little information on the specific role of comparable Si (sodium silicate) concentrations in salinity stress reduction. As a result, the current study investigated the impact of two distinct Si concentrations (1 and 5 mM) on the physiochemical features of the “mung bean,” one of the most extensively cultivated legumes, when exposed to salinity (10, 20, and 50 mM NaCl). Salinity stress reduced growth variables such as biomass, nodule formation, plant length, height, and photosynthetic measures, which were mitigated by silicon supplementation at 5 mM sodium silicate. The inclusion of silicon increased the expression of photosynthetic proteins such as PSI, PSII, and LHCs under salt stress. Salinity stress also caused oxidative damage in the mung bean in the form of hydrogen peroxide (H2O2) and superoxide radical (O2−), leading in increased lipid peroxidation (MDA) and electrolyte leakage. In contrast, 5 mM sodium silicate tends to scavenge free radicals, reducing lipid peroxidation (MDA) and electrolyte loss. This was linked to significant silica deposition in the leaf epidermis, which eventually functioned as a mechanical barrier in mitigating the deleterious effects of salt stress. Si supplementation also decreased Na+ uptake while increasing K+ uptake. Silicon, specifically 5 mM sodium silicate, was found to minimize salinity stress in mung bean by altering physio-chemical parameters such as photosynthetic machinery, Na+/K+ homeostasis, mechanical barriers, osmolyte production, and oxidative stress.